2021
DOI: 10.1111/jnu.12627
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Anger Expression in the Relationship of Work Stress with Burnout among Hospital Nurses Depending on Career Experience

Abstract: Objectives This study examined the mediating effects of anger expression in the relationship between work stress and burnout among nurses with more than or less than 3 years of career experience. Methods A cross‐sectional study was conducted with 454 nurses working at three university hospitals in South Korea. Nurses completed a survey consisting of demographic questions, the Maslach Burnout Inventory, the Work Stress Scale, and the Korean version of the Anger Expression Inventory. A multiple‐group mediation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Therefore, nurses’ work stress during the pandemic should be evaluated from the perspective of occupational health. Studies confirm a relationship between work stress, social support, and more work experience among nurses ( Adekanmbi & Ukpere, 2020 ; Lee et al, 2021 ). Perceived organisational support refers to employees’ perception that organisations acknowledge their contributions ( Robaee et al, 2018 ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, nurses’ work stress during the pandemic should be evaluated from the perspective of occupational health. Studies confirm a relationship between work stress, social support, and more work experience among nurses ( Adekanmbi & Ukpere, 2020 ; Lee et al, 2021 ). Perceived organisational support refers to employees’ perception that organisations acknowledge their contributions ( Robaee et al, 2018 ).…”
Section: Introductionmentioning
confidence: 93%
“…Similar to many countries, the Korean healthcare system has experienced challenges during the COVID-19 pandemic ( Heo et al, 2021 ), with a significant impact on healthcare institutions, requiring more frontline healthcare providers and increased work capacity ( Liu et al, 2020 ). As burdens on overextended healthcare systems intensified and the pandemic prolonged, healthcare providers increasingly struggled because of high intensity demands and mental health issues, including depression and burnout ( Kakemam et al, 2021 ; Lee et al, 2021 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, participants experienced increased cynicism and anger towards other patients and those in their personal life. Anger has been identified as a grief reaction in nurses coping with the death of a patient, and nurse burnout following stressful situations may in part be mediated by suppressing this emotion (Khalaf et al, 2018; Lee et al, 2021). Knowing this, it is important for nursing leaders to allow for a safe space for nurses to verbalise their anger following paediatric resuscitations.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies (Glomb & Liao, 2003;Henle, 2005;NG & Feldman, 2008;Dirican & Erdil, 2016;Pletzer, 2021), which found that adult workers engage in more CWBs than older employees. A possible explanation for this result is that it makes sense that as people get older and more experienced, their levels of anger decrease because they learn how to deal with it more effectively (Lee et al, 2021). Furthermore, evidence suggests that senior employees are more trustworthy than younger ones (Hauk et al, 2019).…”
Section: The Variance Among Employees' Age Groups Regrading Cwbsmentioning
confidence: 99%